In Search of the Goddess: Creating a Feminist Motherline for Mother-Daughter Connection and Empowerment - O’Reilly, Andrea (Journal of the Motherhood Initiative for Research and Community Involvement, 2018)
The term “motherline,” as Sharon Abby explains, “is a term that was first used by Jungian psychologist Naomi Lowinsky to describe the process of reclaiming aspects of the feminine self that have become lost, forgotten or repressed” (844). Current literature on motherlines conveys and confirms the potential of the motherline to empower women to achieve a reclaimed and renewed feminine identity. However, what is not specifically examined in the literature on motherlines is how a woman may reclaim aspects of the feminine self when she is disconnected from her familial and ancestral motherline. Drawing upon the insights of African American and feminist writings on the motherline, this article explores how women may resurrect a lost motherline through a psychic and embodied remembering of, and reconnection to, their ancestral lineage. The article begins with a discussion of the motherline as theorized in womanist and feminist literature, and then visits my own struggle to create a motherline for me and my daughters from a place of psychic and familial dislocation. The article concludes with narrative reflections written by me and my youngest daughter, Casey, about our 2015 journey to Ireland that explores how, in our search for the Goddesses of our Celtic lineage, we created a motherline for connection and empowerment.